DESIGN AND ANALYSIS OF HONEYCOMB STRUCTURE COOLING FIN - S., Maidin; N.F., Azmi (Journal of Advanced Manufacturing Technology (JAMT), 2015)
Cooling fin is an important component to assist thermal management inside high performance light emitting diode (LED). The area of cooling fin plays an important role to drive the heat away from the LED. It is essential to have good thermal management to optimize the working life of high performance LED and its illuminating efficiency. This paper studies a proposed redesigned honeycomb structure cooling fin for high performance LED. Analysis of thermal base on conduction and natural convection was conducted. Aluminum Alloy was selected as the material of the honeycomb structure cooling fin. 3D modeling was done to create the design of the cooling fins structure. The model was tested with thermal analysis and the results for both cooling fins were compared. The result showed that the honeycomb structure cooling fin achieved the optimum surface area for thermal management of high performance LED street lamp. This study showed that honeycomb structure cooling fin have the potential to increase the working life of high performance LED and its illuminating efficiency. Further study should be conducted in the application of honeycomb structure cooling fin in other electronic or electrical devices.